NCL 3.1 Enhanced DTV Profile - Soares, Luiz Fernando Gomes; Lima, Guilherme; Soares Neto, Carlos de Salles (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
NCL (Nested Context Language) in its current version 3.0 has been evaluated both through empirical and analytic methods, which have provided important insights on how to interpret the meaning and impact of syntactic and semantic features of NCL on human cognition. The several evaluations raised some very interesting issues that lead to the design of the new NCL 3.1 version. This paper presents the new features of the NCL 3.1 Enhanced Digital TV profile and gives good reasons for them, recognizing the evaluation results.